2017
DOI: 10.1007/s13770-017-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact Coculture Reveals a Comprehensive Response of Chondrocytes Induced by Mesenchymal Stem Cells Through Trophic Secretion

Abstract: Coculture between mesenchymal stem cells (MSCs) and chondrocytes has significant implications in cartilage regeneration. However, a conclusive understanding remains elusive. Previously, we reported that rabbit bone marrowderived MSCs (rbBMSCs) could downregulate the differentiated phenotype of rabbit articular chondrocytes (rbACs) in a non-contact coculture system for the first time. In the present study, a systemic investigation was performed to understand the biological characteristics of chondrocytes in coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(51 reference statements)
1
0
0
Order By: Relevance
“…MSCs in 3D microniches co-cultured with chondrocytes showed GO terms relating to ribosome biogenesis, ECM organization, and positive regulation of cell migration and glycosaminoglycan binding, processes which were similar to those encountered in MSC chondrogenesis [ 70 ]. Chondrocytes in the 3D group showed significant variations in gene expression relating to cellular processes, ECM, and signal transduction, suggesting a comprehensive response that was also observed in other studies using rabbit chondrocytes [ 71 ]. A number of cartilage-related GO terms for both MSCs and chondrocytes in the 3D group suggested that MSCs cultured in microniches had greater potential to maintain in vitro chondrogenesis and maintenance of the original chondrocyte phenotype.…”
Section: Discussionsupporting
confidence: 79%
“…MSCs in 3D microniches co-cultured with chondrocytes showed GO terms relating to ribosome biogenesis, ECM organization, and positive regulation of cell migration and glycosaminoglycan binding, processes which were similar to those encountered in MSC chondrogenesis [ 70 ]. Chondrocytes in the 3D group showed significant variations in gene expression relating to cellular processes, ECM, and signal transduction, suggesting a comprehensive response that was also observed in other studies using rabbit chondrocytes [ 71 ]. A number of cartilage-related GO terms for both MSCs and chondrocytes in the 3D group suggested that MSCs cultured in microniches had greater potential to maintain in vitro chondrogenesis and maintenance of the original chondrocyte phenotype.…”
Section: Discussionsupporting
confidence: 79%